2020
DOI: 10.1021/acsami.0c17030
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity 3D Nanoprinting of Plasmonic Gold Nanoantennas

Abstract: The direct-write fabrication of freestanding nanoantennas for plasmonic applications is a challenging task, as demands for overall morphologies, nanoscale features, and material qualities are very high. Within the small pool of capable technologies, three-dimensional (3D) nanoprinting via focused electron beam-induced deposition (FEBID) is a promising candidate due to its design flexibility. As FEBID materials notoriously suffer from high carbon contents, the chemical postgrowth transfer into pure metals is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 80 publications
0
36
0
Order By: Relevance
“…A closer look at the take-off region at the substrate revealed that the legs initially grew at steeper angles than after a few hundreds of nanometers (Figure 4a). This increased vertical growth rate at early growth stages together with the observed base broadening [22] can be explained by the much better diffusive replenishment situation close to the substrate, which acts like a much bigger precursor reservoir. With increasing segment length (distance to the substrate), growth gradually approaches a lower growth rate, leading to unwanted curvatures even at low T S .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A closer look at the take-off region at the substrate revealed that the legs initially grew at steeper angles than after a few hundreds of nanometers (Figure 4a). This increased vertical growth rate at early growth stages together with the observed base broadening [22] can be explained by the much better diffusive replenishment situation close to the substrate, which acts like a much bigger precursor reservoir. With increasing segment length (distance to the substrate), growth gradually approaches a lower growth rate, leading to unwanted curvatures even at low T S .…”
Section: Discussionmentioning
confidence: 92%
“…Drawbacks are the low purity due to high carbon contents in as-deposited materials for most precursors [20] and low fabrication speeds with growth rates in the range of tens of nm/s [14]. The removal of carbon contaminants from 3D-FEBID materials is discussed in detail elsewhere [13,21,22], while we address different strategies to tackle the speed issue. Under typical fabrication conditions, the amount of available precursor molecules at deposition sites limit 3D-growth (molecule limited regime [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, studies under a controlled water atmosphere to yield defined manganese oxide deposits could be envisioned. The wealth of various physical phenomena observed in the different manganese oxides could justify similar experiments as carried out for the purification of Pt, Pd, and Au in order to remove C [ 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The controlled and stable fabrication of open helices is a challenging task, as it actually is a re-directed single wire, which has been demonstrated to be problematic, once their lengths approach the micron range [27]. Additionally, varying angles between the directed gas flux and the growth direction arise, which can impact the spatial precision [10,21,28]. As a starting point, helices with a diameter of 500 nm were deposited at a range of constant DTs, i.e., patterning velocities at adjusted blur values aimed to result in a target inclination of 45 • .…”
Section: Part Ii-helix Fabricationmentioning
confidence: 99%
“…As a consequence of the wider beam, the fabricated pillars grew at wider dimensions. In more recent studies, Pablo-Navarro et al and Kuhness et al showed that the diameter of a vertical pillar structure can be modulated by means of the dynamic adjustment of the beam diameter during deposition [21,22]. Addressing 3D-FEBID in particular, Winkler et al employed a defocused electron beam for the growth of so called diving boards.…”
Section: Introductionmentioning
confidence: 99%